Alternative care options and policy choices to support orphans: The case of Mozambique in the context of the SADC. (2nd January 2013) - Shibuya, Tomoko; Taylor, Viviene
Abstract Contextualizing the situation of orphans within the Southern African region and drawing on quantitative and qualitative field research, this article analyses care options and social protection policy for orphans in Mozambique, with its focus placed on children in orphan support centres. Seeking to offer new insights and greater understanding of the experiences of children in care and of the social protection available to them, the research highlights that orphaned children living in informal foster care arrangements are more likely to experience abuse, neglect and maltreatment than those living in non‐governmental care organizations. The research emphasizes the need for a more careful selection of foster families in which children are placed. Recommendations include the need to focus on capacity building and institutional reforms that provide social protection policies for orphaned children as part of an overall social protection floor. The monitoring and evaluation of organizations providing care to orphaned children is deemed a priority.